Vermicomposting: A gender-inclusive solution for sustainable manure management for homestead and high-value crops - Ahmed, Sharif; Debnath, Manik; Miajy, Abdullah; Haque, Abdul; Bhandari, Humnath (International Rice Research Institute, 2024)
Bangladesh is an agricultural country where agriculture sector plays a vital role in accelerating the economic growth. It is therefore important to have a profitable, sustainable, and environment-friendly agricultural system to ensure long-term food security for people. As the population grows, the amount of food needed also increases. However, food safety and security are not obtained due to the excessive use of chemical pesticides and chemical-based fertilizers. Our agriculture is now characterized by excessive use of chemical fertilizers and pesticides, while the application of organic fertilizers remains insufficient. Various natural elements can serve as fertilizers to enhance soil quality, such as vermicompost, green manure, cow dung, and leaf manure, which are all considered natural fertilizers.